Tanggung Jawab Pelaku Usaha Restoran Atas Penyediaan Aksesibilitas Bagi Konsumen Penyandang Disabilitas - Jihan Maisarah; Sarah Selfina Kuahaty; Theresia Louize Pesulima (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Consumers as users of restaurant services include persons with disabilities who have the right to accessibility. However, the reality is that there are still many restaurants in Ambon city which have not fulfilled their obligation to provide accessibility facilities for persons with disabilities.Purposes of the Research: This study aims to examine the accountability of business actors to consumers and consider resolving disputes between business actors and consumers with disabilities in public services. Methods of the Research: The research method used is normative juridical with a statutory approach in the sources of primary, secondary, and tertiary legal materials.  The technique of collecting legal materials is through library research and prescriptive analysis.Results of the Research: The results of this study show the conditions in order to be able to immediately form actions in supervision and guidance as regulated in Article 29 paragraph (1) and Article 30 paragraph (1) to business actors in public services such as restaurants, to ensure the rights of consumers as regulated in the Law. -Consumer protection law. Enforcement of regulations through legal sanctions so that the fulfillment of consumer rights is truly fulfilled. According to the Consumer Protection Act, it can be in the form of a refund, or by providing compensation in accordance with the provisions of the applicable laws and regulations.